Neanderthals Revisited New Approaches and Perspectives - Harvati, Katerina; Harrison, Terry (Vertebrate Paleobiology and Paleoanthropology, 2006)
Recent years have witnessed exciting and important scientific breakthroughs in the study of Neanderthals and their place in human evolution which have transformed our appreciation of this group's paleobiology and evolution. This volume presents cutting-edge research by leading scientists re-examining the major debates in Neanderthal research with the use of innovative state-of-the art methods and exciting new theoretical approaches. Topics addressed include the re-evaluation of Neanderthal anatomy, inferred adaptations and habitual activities, developmental patterns, phylogenetic relationships, and the Neanderthal extinction; new methods include computer tomography, 3D geometric morphometrics, ancient DNA and bioenergetics. The diverse contributions offer fresh insights and advances in Neanderthal and modern human origins research. This is a Volume in The Max-Planck-Institute Subseries in Human Evolution coordinated by Jean-Jacques Hublin, Max-Planck-Institute for Evolutionary Anthropology, Department of Human Evolution, Leipzig, Germany.